Family law in Islam : divorce, marriage and women in the Muslim world - Voorhoeve, Maaike , 1979- (London : I.B.Tauris, 2012)
Using a range of contemporary examples, from polygamy to informal marriage (zawaj 'urfi), and from divorce with mutual agreement (khul') to judicial divorce (tatliq), this volume explores the impact of Islamic law on individuals, families and society alike from Morocco to Egypt and from Syria to Iran.
1. Introduction -- 2. 'She brings up healthy children for the homeland' : morality discourses in Yemeni legal debates -- 3. Reclaiming changes within the community public sphere : Druze women's activism, personal status law and the quest for Lebanese multiple citizenship -- 4. What a focus on 'family' means in the Islamic Republic of Iran -- 5. Rethinking the difference between formal and informal marriages in Egypt -- 6. Waiting to win : family disputes, court reform, and the ethnography of delay -- 7. Divorce practices in Muslim and Christian courts in Syria -- 8. Maktub : An ethnography of evidence in a Tunisian divorce court -- 9. Judicial discretion in Tunisian personal status law
Includes bibliographical references and index
Keywords: Divorce -- Religious aspects -- Islam; Domestic relations (Islamic law); Islamic courts; Muslim women